Screening of Sengkuang (Dracontomelon dao (Blanco) Merr. & Rofe) as Antibacterial Escherichia coli - Ratih Dewi Dwiyanti; Nurlailah Nurlailah (Medical Laboratory Technology Journal, 2022)
Dracontomelon dao (Blanco) Merr. & Rofe has antimicrobial potential, but Dracontomelon dao (Blanco) Merr. & Rofe, originating from Kalimantan, Indonesia, has not been tested for its antibacterial properties and secondary metabolite content. This study aimed to analyze the secondary metabolite content of various Dracontomelon dao (Blanco) Merr leaf extracts. & Rofe and their antibacterial effectiveness against Escherichia coli. The study used 96% ethanol extract, ethyl acetate, petroleum ether, and chloroform by maceration simplicia leaves. Dracontomelon dao (Blanco) Merr. & Rofe is from South Kalimantan, Indonesia. Antibacterial testing was carried out using the agar diffusion method, the Minimum Inhibitory Concentration (MIC) method, and the Minimum Bactericidal Concentration (MBC) method. The results showed that the triterpenoid content was the highest in all extracts, namely ethanol extract 669.8 ± 2,000 mg/ml, ethyl acetate 90 ± 7,638 mg/ml, petroleum ether 792, 800 ± 4,583 mg/ml, chloroform 615, 467 ± 0,577 mg/ml. ml. The antibacterial test using the well diffusion method showed the best inhibition of bacterial growth in ethanol extract, with the largest inhibition zone of 24 mm at a concentration of 500 mg/ml. The study's conclusion was the extract of ethanol, ethyl acetate, petroleum ether and chloroform from the leaves of Dracontomelon dao (Blanco) Merr. & Rofe contains the same five secondary metabolites: flavonoids, alkaloids, saponins, tannins and triterpenoids. All types of extracts showed varying abilities to inhibit the growth of Escherichia coli. Further research is needed on the antibacterial properties of Dracontomelon dao (Blanco) Merr extract. & Rofe, especially on the active substance triterpenoid, which is the largest content in all types of extracts.